Mitochondria in Sporadic Amyotrophic Lateral Sclerosis - Swerdlow, Russell H.; Parks, Janice K.; Cassarino, David S.; Trimmer, Patricia A.; Miller, Scott W.; Maguire, David J.; Sheehan, Jason P.; Maguire, Robyn S.; Pattee, Gary; Juel, Vern C.; Phillips, Lawrence H.; Tuttle, Jeremy B.; et al. (Experimental neurology, 1998)
Mitochondria are abnormal in persons with amyotrophic lateral sclerosis (ALS) for unknown reasons. We explored whether aberration of mitochondrial DNA (mtDNA) could play a role in this by transferring mitochondrial DNA (mtDNA) from ALS subjects to mtDNA-depleted human neuroblastoma cells. Resulting ALS cytoplasmic hybrids (cybrids) exhibited abnormal electron transport chain functioning, increases in free radical scavenging enzyme activities, perturbed calcium homeostasis, and altered mitochondrial ultrastructure. Recapitulation of defects previously observed in ALS subjects and ALS transgenic mice by expression of ALS mtDNA support a pathophysiologic role for mtDNA mutation in some persons with this disease.